Adapting Poe : re-imaginings in popular culture - Perry, Dennis R.; Sederholm, Carl Hinckley (Palgrave Macmillan, 2012)
"Adapting Poe collects new interdisciplinary essays by leading scholars that combine the latest work in adaptation theory with fresh discussions of Poe, his work, and popular culture. The book examines a range of genres and media into which Poe has been adapted, such as film, comic art, music, literary criticism, promotional campaigns, television, and internet videos. Each essay will help readers re-evaluate Poe's influence not only on popular culture today, but also as a significant figure in its development. The book also goes far to demonstrate Poe's pervasive and continuing relevance to the images and ideas of contemporary culture"--